Lu-Hf geochronology of ultra-high-pressure eclogites from the Tromso-Nappe, Scandinavian Caledonides: evidence for rapid subduction and exhumation - Fassmer, K.; Martinet, I; Miladinova, I; Sprung, P.; Froitzheim, N.; Fonseca, R. O. C.; Muenker, C.; Janak, M.; Kullerud, K. (SPRINGER, 2020)
Geochronology of ultra-high-pressure metamorphic rocks is able to constrain the timing and rates of subduction-zone processes. Lu-Hf garnet dating has the potential to yield information about the timing of the prograde evolution of subducting rocks under increasing pressure. In combination with other methods, it thus allows constraining the complete P-T-t path with high precision. Ultra-high-pressure eclogites from the Tromso Nappe, the structurally highest tectonic unit of the Scandinavian Caledonides in northern Norway, were dated using Lu-Hf geochronology on garnet. A sample from Tromsdalstind yielded an age of 448.3 +/- 3.6 Ma, interpreted as dating prograde garnet growth due to preserved zoning in the major-element and Lu contents of garnet grains. A sample from the diamond-bearing locality Tonsvika yielded an identical age of 449.4 +/- 3.3 Ma. Garnet from this sample shows a weak zoning in Ca content and near-homogeneous Lu content. These ages are identical within error among each other and with published U-Pb ages of peak-eclogite-facies zircon and rutile/titanite from exhumation-related leucosome veins. Consequently, the entire subduction-exhumation cycle leading to the ultra-high-pressure eclogites lasted only very few millions of years during the Late Ordovician.